Music streaming services: understanding the drivers of customer purchase and intention to recommend - Barata, Mariana Lopes (2021)
Barata, M. L., & Coelho, P. S. (2021). Music streaming services: understanding the drivers of customer purchase and intention to recommend. Heliyon, 7(8). https://doi.org/10.1016/j.heliyon.2021.e07783